Mechanical Characterization of Epoxy Polymer Concrete Containing Fly Ash - Bedi, Raman; Gupta, Nagendra Kumar (Journal of Research Updates in Polymer Science, 2013)
Polymer concrete is a composite material made of aggregates and polymeric resin as a binder. The applications of polymer concrete is limited not only to the domain of civil engineering but it has got inroads in to structural applications in Machine tool structures. Till date no standard mix design procedures are available for polymer concrete systems. In this research, Polymer concrete samples were made using epoxy resin as a binder, fly ash as a filler and marble waste as aggregate. The various mix proportions were developed using concept of mixture design of experiments. Compressive and flexural strength was evaluated for each composition of polymer concrete thus obtained. The effect of variables such as epoxy resin, fly ash and aggregates were analyzed. An optimum mix composition has been developed using the regression equations. The coefficient of correlation (R-Square) between the experimental value and predicted value was found to be high near about one proving the fitness of the model.